Expression and Functional Study of BcWRKY1 in Baphicacanthus cusia (Nees) Bremek - Zeng, Meijuan; Zhong, Yongjia; Guo, Zhiying; Yang, Huiyong; Zhu, Haisheng; Zheng, Liling; Diao, Yong (Frontiers in Plant Science, 2022)
Baphicacanthus cusia (Nees) Bremek (B. cusia) is an important medicinal plant. Its effective substances including indigo and indirubin are metabolites in indoleacetate metabolic pathway. Based on a previous transcriptome sequencing analysis, a WRKY transcription factor, BcWRKY1, in B. cusia was identified, showing significant correlation with effective substances from B. cusia. In this study, BcWRKY1 was cloned by reverse transcription-polymerase chain reaction (RT-PCR). Further analysis showed that the BcWRKY1 gene was 916 bp in length, containing three exons and two introns. The open reading frame (ORF) of BcWRKY1 was 534 bp in length and encoded a WRKY domain-containing protein with 177 amino acids residues. Subcellular localization showed that BcWRKY1 protein was mainly localized in the nucleus. It could bind to the W-box motif and its role in transcriptional activation was confirmed in yeast. The function of BcWRKY1 was investigated by overexpressing BcWRKY1 in Arabidopsis thaliana. Metabolic profiles in wild type and BcWRKY1-OX1 transgenic Arabidopsis thaliana were analyzed with LC-MS. The results showed that the metabolic profile was significantly changed in BcWRKY1-OX1 transgenic Arabidopsis thaliana compared with wild type. Furthermore, indole-related metabolites were significantly increased in BcWRKY1-OX1 transgenic Arabidopsis thaliana, and the metabolic pathway analysis showed that flavonoid biosynthesis was significantly enriched. Overexpression of BcWRKY1 significantly changed flavonoid and indole metabolism and indole-related metabolites were significantly upregulated. We postulated that the BcWRKY1 transcription factor might be involved in the regulation of effective substances metabolism in B. cusia.